SFMBT2 regulates plumage color via serum metabolites in Chinese Anyi tile-like gray chickens - Jiguo Xu; Qin He; Jishang Gong; Xuewen Chai; Qiao Xu; Xinwei Xiong (Poultry Science)
ABSTRACT: Plumage color is an important characteristic of chicken breeds, and molecular genetic research is significant for resource conservation and product quality control. Anyi tile-like gray chicken is a high-quality local chicken breed resource generated through long-term natural selection and artificial breeding in China. However, the molecular mechanisms underlying plumage color formation in Anyi tile-like gray chickens remain unclear. In this study, nontargeted liquid chromatography and tandem mass spectrometry (LC–MS/MS) was performed to identify serum metabolites associated with plumage color in 93 Anyi tile-like gray chickens, including 60 tile-like gray and 33 black chickens. Notably, 12 serum metabolites were significantly enriched in Anyi tile-like gray chickens, including deoxyuridine and inosine, which were the key biomarkers distinguishing tile-like gray chickens from black chickens. Additionally, nine serum metabolites were significantly enriched in black chickens. Moreover, we identified 225 significant SNPs (P < 9.71 × 10−8) on chromosomes 1, 2, 3, 4, 11, 15, and 21 that were associated with deoxyuridine, inosine, 3-hydroxybenzoic acid, and L-methionine S-oxide through metabolome genome-wide association studies (mGWAS). Importantly, chromosome 1 harbored a region, 172.79-kb, which was the most likely quantitative trait locus (QTL) interval. RNA sequencing (RNA-seq) and quantitative reverse transcription polymerase chain reaction (qRT-PCR) showed that SFMBT2 was the only differentially expressed gene in the QTL interval, and its expression was correlated with the abundance of specific serum metabolites. Conclusively, SFMBT2-mediated changes in serum metabolites contribute to plumage color development in Anyi tile-like gray chicken. This study provides important insights into the interaction between serum metabolites and host genes, and offers a theoretical basis for the breeding of Anyi tile-like gray chickens.